2011
DOI: 10.3109/00365548.2011.600326
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria outbreak in Norway: Lessons learned

Abstract: We describe an outbreak of diphtheria in Norway that occurred in 2008 and affected 3 unvaccinated family members. The epidemic caught the public health system off-guard on most levels; the diagnosis was distrusted due to its rarity, no diphtheria anti-toxin was available, and notification procedures were not rigorously followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…There was no dissemination outside of a close family contact whose household the index case stayed at overnight; this echoes the experience of investigators of a household outbreak of toxigenic diphtheria in Norway in 2008 where there were three cases in unimmunised individuals within the same family [ 20 ]. These cases developed a confluent, thick yellow membrane across their tonsils and peritonsillar tissue.…”
Section: Discussionsupporting
confidence: 66%
“…There was no dissemination outside of a close family contact whose household the index case stayed at overnight; this echoes the experience of investigators of a household outbreak of toxigenic diphtheria in Norway in 2008 where there were three cases in unimmunised individuals within the same family [ 20 ]. These cases developed a confluent, thick yellow membrane across their tonsils and peritonsillar tissue.…”
Section: Discussionsupporting
confidence: 66%
“…As with cases in other industrialized countries, investigations could not identify a source of infection ( 4 , 7 ). Asymptomatic carriers remained a possibility because studies have reported bacterial carriage in vaccinated persons and nontoxigenic strains that underwent phage conversion ( 5 , 6 , 12 15 ). Because the patient had an unknown vaccination history, missing childhood vaccinations might have put him at risk for infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this outbreak, a high proportion of adults were affected, potentially due to disruption of health services resulting in poor vaccine coverage (114, 115) and reduced “natural” exposure over the preceding decades, resulting in antibody titers below protective levels (116118). In recent years, multiple outbreaks, or potential transmission clusters have been reported in: Bangladesh (119, 120), Brazil (121), Colombia (122), Germany (30, 35), India (123–125), Indonesia (126), Laos (127), Norway (128), Nigeria (129), Poland (130), Spain (38), South Africa (36, 131), Syria (132), Switzerland (31), Thailand (114), the United Kingdom (37), Venezuela (133, 134), and Yemen (135). The global list of affected countries indicates that (i) the disease is remains poorly controlled, (ii) the main burden lies in low-income countries, and (iii) local and global surveillance should be intensified in order to better control the disease.…”
Section: The Return Of An Old Foementioning
confidence: 99%